Możliwości kompensacji skutków niżu demograficznego - z perspektywy szkolnictwa wyższego = Possibilities of compensating the effects of demographic decline - from the perspective of higher education - Borowicz, Ryszard (1945-2014) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Polish universities have just started suffering from the effects of demographic decline whose downward trend shows that this negative situation may reverse only in two decades. According to this fact - precisely speaking gross enrolment ratio - the number of students will fall by one third. The consequences for universities (especially non-state ones) seem to be obvious - closing unpopular fields of studies, bankruptcy of schools or their consolidation. However, it is a very advantageous situation from the point of view of educational policy - there is a feasibility to carry out profound reforms.
Keywords: szkolnictwo wyższe; demografia; demograficzne zmiany; szansa; zmiana; Polska